Beef Cattle Feed Requirements - Kuhl, Gerry L.; Jones, Rodney D.; Marston, Twig (My University, 2002)
This publication describes the feed requirements for beef cattle for Kansas beef producers.
MF264_2002_10
Keywords: MF264; Livestock; MF